UPAYA PEMERINTAH INDONESIA DALAM MENJAGA WILAYAH PERBATASAN INDONESIA-VIETNAM TAHUN (2010-2014) - Nurul Atika; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research that the study of diplomacy and strategy analyzes about Indonesian government's efforts in maintaining the border region Indonesia-Vietnam years (2010-2014). The purpose of this research is to explain about general conditions Indonesia-Vietnam defence, the condition of Indonesia-Vietnam border region, and Indonesian government’s efforts in maintaining the border region Indonesia-Vietnam years (2010-2014).Indonesia-Vietnam border lies between the Sekatung island and Condore island in South China Sea. Indonesian government attempted to keep the border region because Sekatung Island is one of the outer islands are disturbed to conflict. Moreover Indonesia has border issues with Vietnam. The problems that Indonesia has not been completed entire sea border agreement with Vietnam and the violation of the territorial sovereignty (illegal fishing) which is rife in the waters of Natuna Islands. That problems in Indonesia-Vietnam border, it will threaten the national security and defense Indonesia.This research used qualitative methods which is done by explanning the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, official documen, article, and website. The theoretical framework applied in this research are realism perspective, security concept, nation-state analysis and national security theory. National security is a form of a country's ability to provide a protection for each country from external threats indication. The persective usedKeyword: effort, national security, defence,boundary, the continental shelf boundary, exclusive economic zone